STUDY OF 3-BUS ELECTRIC POWER SYSTEM POWER FLOW USING THE NEWTON-RAPHSON METHOD - VICKY SALAMENA (CV KULTURA DIGITAL MEDIA, 2023)
This study is a study of power flow in an electric power system consisting of three buses which intends to find the magnitude of voltage and angles of voltage on each bus, as well as the power loss on each line. Power system modeling for power flow studies produces mathematical equations that can be solved simultaneously. One of the numerical methods to solve this problem is to use the Newton-Raphson method. To solve the power flow, the system is assumed to operate in a three-phase balanced condition and modeling is done for one phase which represents the other two phases. This requires that there are four quantities on each bus, namely active power and reactive power that enter the bus with these two quantities known on each bus. Furthermore, the magnitude of the voltage and the phase angle of the voltage at the bus, these two quantities will be calculated in the power flow study. The non-linear algebraic equation for the power flow model is linearized using the Taylor series to become a matrix equation in which there is a Jacobian matrix. This matrix equation is solved simultaneously (simultaneously) using the Newton-Raphson iteration method. Iteration results show that the value of the voltage angle of Bus-2 is 1,33 electric-degre, the angle of voltage of Bus-3 is -5,38 electric-degre and the amplitude of the voltage of Bus-3 is 0.9343-pu. Bus-1 as Swing-Bus injects active power of 99.50 MW and reactive power of 26.00 MVAr, Bus-2 as Bus-PV provides active power of 400.58 MW and reactive power of 418.57 MVAr and Bus-3 as Bus-load (PQ-Bus) receives active power of 219.00 MW from Bus-1 and 281.08 MW to fulfill a scheduled active load of 50 0.08 MW and receives 143.14 MW of reactive power from Bus-1 and 206.97 MVAr to meet the scheduled reactive power of 350.11 MVAr. There is no active power loss on each line because in the calculation the line resistance is ignored, while reactive power losses are present on each line, namely line 1-2 of 7.27 MVAr, line 1-3 of 31.36 MVAr and line 2-3 of 55.83 MVAr.